Make it small, the house of the big idea : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Te Ao, Kate (Massey University, 2022)
This exegesis discusses a range of recent sculpture and installation by Kate Te Ao. Pīpīwharauroa (2020), Make it small, the house of the big idea (2021) and Untitled (2021) are discussed in relation to colonial history, Pākehātanga, decolonisation and what Moana Jackson suggests we might call restoration. These works are located in relation to antiform and the work of other artists who approach art making as a conversation between space and materials, objects and imagination. Rather than being a direct or didactic expression of ideas the works occupy an active, processual, and generative space in which materials, objects and space combine to open territory for multiplicity, humour, grief and hope.
Keywords: 360602 Fine arts